Green Synthesis of Aluminum Silicate and Aluminum Iron Oxide Nanocomposites for Industrial Applications - Muhammed Saad Shabir; Hina Zain; Moin Maqsood; Aysha Bukhari; Ammara Nazir (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Nano chemistry is revolutionizing the chemical industry. This research targets the green synthesis of Al-Si and Al-Fe nanocomposites and their application in the cement industry to produce durable cement coating. The nanocomposites were prepared by incorporating the green ingredients as reducing and stabilizing agents followed by the direct heating and calcination of the samples. The X-ray diffraction analysis and SEM were performed to confirm crystallinity and the nano-dimensional structure of the prepared nanocomposites. The SEM micrographs of Al-Si and Al-Fe nanocomposites provided the sizes as 15-37 nm and 17-61 nm, respectively. BET analysis revealed the surface area as 1.084 m2/g and 0.884 m2/g respectively, for Al-Si and Al-Fe nanocomposites. These were applied in cement mortar and stability was checked for 07 and 28 days. The samples with 07 days of stability time showed an increase while the samples with 28 days showed a decrease in compressive strength.